Omerta - Puzo, Mario (New York : Ballantine Books, 2004)
When Don Raymonde Aprile, an old-school Mafia leader who has retired, is killed, it is not his children, who were kept strictly away from their father's business, who seek to avenge him, but his Sicilian-born ward, Astorre, the son of an even greater Mafia chieftain.
Keywords: Mafia -- Fiction; Detective and mystery fiction